Infection prevention knowledge and perceptions: a nationwide survey among nurses and physicians in adult intensive care units in Finland - Kirsi Terho; Eliisa Löyttyniemi; Esa Rintala; Sanna Salanterä (PLoS ONE, 2025)
Background Healthcare-associated infections are a major complication of care for patients in intensive care, causing costs and additional mortality. Infection prevention practices, such as hand hygiene, have been suboptimal globally. This study aimed to explore the level of knowledge and perceptions of critical care staff regarding healthcare-associated infections as insufficient knowledge contributes to an increased burden of these infections. Methods A nationwide survey of physicians and nurses working in intensive care units of Finnish tertiary care hospitals was conducted to gain knowledge and explore perceptions regarding the prevention of healthcare-associated infections in intensive care units. Descriptive statistics were used to describe the study data, and a mainly nonparametric method was used to compare the groups. Results The respondents demonstrated moderately good knowledge of hand hygiene and infection prevention, with a median of 36 correct responses (Q1, Q3: 34, 37). However, there were notable gaps in their knowledge in infection prevention regarding the routes of infection transmission, with a median score of 4 (Q1, Q3: 4, 6). Conversely, perceptions of infection prevention were generally positive. The median score for perceptions was 51 (Q1, Q3: 47, 55), but no significant association was found between perceptions and knowledge levels. Conclusions The level of knowledge about healthcare-associated infections is not satisfactory. In particular, there is a lack of in-depth understanding of the mechanisms of infection transmission and prevention. Providing unit-tailored feedback on performance, along with education on the transmission mechanisms and infection prevention for healthcare workers is essential.